This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Saturday, June 12, 2010 Page 1 Mathematics 1225A (Online) Midterm Examination Students Name ( Print ) Students Number 1. Evaluate parenleftbigg 9 1 8 2 / 3 3 2 parenrightbigg 1 2 . A : 2 3 B : 1 C : 2 D : 2 E : 6 Solution: parenleftbigg 9 1 8 2 / 3 3 2 parenrightbigg 1 2 = parenleftbigg (3 2 ) 1 (2 3 ) 2 / 3 3 2 parenrightbigg 1 2 = parenleftbigg 3 2( 1) 2 3(2 / 3) 3 2 parenrightbigg 1 2 = parenleftBig 3 2 ( 2) 2 2 parenrightBig 1 2 = ( 3 2 2 ) 1 2 = ( 1(2 2 ) ) 1 2 = 2 2(1 / 2) = 2 Another Approach: 9 1 = 1 9 and since 8 1 / 3 = radicalbig [3]8 = 2 then 8 2 / 3 = 2 2 = 4. And of course 3 2 = 1 3 2 = 1 9 , so we have: parenleftbigg 9 1 8 2 / 3 3 2 parenrightbigg 1 / 2 = radicalBigg 1 9 4 1 9 = 4 = 2 2. Express log 2 9 2 log 2 6 as simply as possible. A : 2 B : 0 C : 1 8 D : 1 4 E : log 2 9 Solution: log 2 9 2 log 2 6 = log 2 9 log 2 6 2 = log 2 9 log 2 36 = log 2 parenleftbigg 9 36 parenrightbigg = log 2 parenleftbigg 1 4 parenrightbigg = log 2 2 2 = 2 Another Approach: log 2 9 2 log 2 6 = log 2 3 2 2 log 2 (3 2) = 2 log 2 3 2(log 2 3+log 2 2) = 2 log 2 3 2 log 2 3 2 log 2 2 = 0 2(1) = 2 3. If f ( x ) = 1 + ( 2 3 x 1 ) 4 and f ( a ) = 9 8 , what is the value of a ? A : 1 4 B : 1 12 C : 15 4 D : 97 32 E : ln 9 ln 8 4 + 3 Solution: We have f ( a ) = 1 + ( 2 3 a 1 ) 4 which must equal 9 8 . We see that: 1 + ( 2 3 a 1 ) 4 = 9 8 ( 2 3 a 1 ) 4 = 9 8 1 = 1 8 2 4(3 a 1) = 2 3 4(3 a 1) = 3 12 a 4 = 3 12 a = 1 a = 1 12 Mathematics 1225A (Online) Midterm Examination Saturday, June 12, 2010 Page 2 4. Which of the following most closely resembles the graph of y = log 2 x ? A : B : C : D : E : Solution: We know that for any b > 1, the graph of y = log 2 x is increasing everywhere, is asymptotic to the yaxis and approaches as x + , and that it passes through the point (1 , 0). That is, it looks like the graph in answer C. But if you couldnt remember that, we know that for f ( x ) = log 2 x , f is defined only for positive values of x , and has derivative f ( x ) = 1 x ln 2 . Since x > 0 everywhere in the domain of f (and hence also everywhere in the domain of f ), and ln 2 > 0, then f ( x ) > 0 throughout its domain, so f is increasing everywhere. Also, f (1) = log 2 1 = 0, so the graph of y = f ( x ) passes through (1 , 0). (And thats enough to eliminate the other graphs.) 5. Find f ( x ) if f ( x ) = x 2 ln  x  . A : 1 + 2 ln  x  B : 3 + 2 ln  x  C : x + 2 x ln  x  D : 2 x 2 E : 0 Solution: We know that d dx [ln  x  ] = 1 x . So using the product rule, we get: f ( x ) = x 2 parenleftbigg 1 x parenrightbigg + (2 x ) ln  x  = x + 2 x ln  x  Using the product rule again for the second term, we get: f ( x ) = 1 + 2 x parenleftbigg 1 x parenrightbigg + 2 ln  x  = 1 + 2 + 2 ln  x  = 3 + 2 ln ...
View Full
Document
 Summer '09
 Math

Click to edit the document details